Peningkatan Kemampuan Guling Depan Menggunakan Pendekatan Contextual Teaching Learning Dengan Metode Bantuan Teman pada Siswa Kelas V SDN 3 Teluk Palinget Tahun Pelajaran 2021/2022 - Suratmi, Titin (Institut Teknologi Pendidikan Indonesia, 2022)
The results of the Flooring Exercise learning material for Class V Semester 2 forward roll at SD Negeri 3 Teluk Palinget were incomplete, this can be seen from the daily value of learning forward roll for class V Semester 2 for the 2021/2022 academic year. The ability of students in mastering the forward roll motion can also be seen from the Minimum Completeness Criteria (KKM) score of only 16% or 4 students who have completed it, while 84% or 21 students have not completed according to the KKM set by SD Negeri 3 Teluk Palinget Kecamatan Selat. The completeness score is 65. The problem in this research is whether the use of the peer assistance method can improve the learning outcomes of fifthgrade students at SD Negeri 3 Teluk Palinget, Selat District, Kapuas Regency for the 2021/2022 academic year. This study uses Classroom Action Research in its implementation consisting of 2 cycles. Each cycle is held once a meeting which consists of 4 stages, namely, planning, implementation, observation (observation), and reflection. The research subjects were fifth-grade students at SD Negeri 3 Teluk Mostet, Selat District. Totaling 25 students consisting of 15 male students and 10 female students. The instruments used in research are performance, tests, and observations. Based on the results of the study in cycle 1 students who completed 84% or 5 students or 20% did not complete and in cycle 2 students who completed 24 or 96% and did not complete 1 student or 4% of class V students as many as25 students. Based on the results of the research above, it can be concluded that the peer assistance method in learning floor exercise on forward roll material, can improve learningoutcomes for fifth-grade students at SD Negeri 3 Teluk Palinget for the 2021/20221 academic year.